(untitled) (Altre Modernità, 2019)
The video presented here is designed as a guide for filming sign language poetry. Using a series of takes of a single poem in Brazilian Sign Language “Fallen Angel” (in Portuguese “Anjo Caido”) by the Brazilian sign language poet Fernanda Machado, the video shows options for filming and editing a piece of sign language poetry. This short video complements the longer article in this collection “Representing Libras Poetry on Video” by Fernanda Machado.